Spectrophotometric determination of sulphite and thiamin hydrochloride using proton transfer reaction-application to water sample and pharmaceutical formation - Bassima A. Abed Al-Hadi (Tikrit Journal of Pure Science)
In this research, an easy, acurate and rapid spectrophotometric method for determination of sulphite and thiamine hydrochloride is described. This method used proton transfer reaction between sulphite ion with alizarine at (pH 6.73) to develop red colour adduct that bears maximum absorption at 524 nm. This method was developed to determination of thiamine hydrochloride by bleaching the red colour (alizarine-sulphite product) at the optimum conditions established for the determination of sulphite. Beer’s law is obeyed in the concentration range (10-1000) μg/25ml (0.4-40) of sulphite and 10-1500, μg/25ml (0.4-60) for thiamine hydrochloride at the selected wavelength, the molar absorbtivity 2.6×104 l.mol-1.cm-1 for SO32- and 3.37×104 l.mol-1.cm-1 for thiamine hydrochloride, Sandell's index for sensitivity 0.00307 μg .cm-2 for sulphite  and 0.0100 μg .cm-2  for B1, the precision (RSD) of the method is ±0.23- ± 0.51% sulphite and ±0.15- ±0.25 thiamine hydrochloride. Good recoveries of sulphite and thiamine hydrochloride from water samples and pharmaceutical formation are achieved using the proposed method.